No Product Lifetime! Why products fails pre-consumer - Laursen, Linda Nhu; Barros, Mário; Nielsen, Christina; Nøkleby, Caroline; Nielsen, Katrine (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Approximately 40% of new product introduction fail when entering the market. Thus valuable resources are spent producing products that never achieve a product lifetime with any users. Companies tend to remove products from their portfolio because of poor sales figures or because they are no longer representing the company’s strategies, but they do so without reflecting on why these exact products failed. This tendency might lead to products repeating the same mistakes that are destined to fail. The purpose of this paper is to investigate failed products from small Danish design companies in order to learn from these mistakes and prevent them from happening again. Factors leading to product failure have been studied by analyzing 35 specific products from two small Danish design companies. By examining the companies’ own reasons for discontinuing these products, the study identifies key contributing factors, including portfolio management, product insecurities, and reliance on existing product success.